Advancing Frontier Nanophysics in Time of Analytical Chemistry: Who to educate first? - Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2020)
Frontier nanophysics in conjunction with nanomedicines, nanoscience and nanotechnology (NNN) developed before the science of analytical chemistry has been very challenges with many competitive obstacles to improve the accuracy and precise nm measurements in order to find out the point of its main chemical structure compositions, uniformity and the concentration contents to each substance. Moreover, exotics nanomaterials either in pure organic and inorganic compound or in hybrid organic-inorganics nanomaterials have shown their remarkable as well as attractive impacts in many nanotechnology and related industrial applications such as in ultrafast picosecond or femtosecond telecommunication integrated circuits and devices system, cosmetics and beauty products, as well as health or pharmaceutical drugs and herbal medicines. In this short communication paper, one explains how to educate first those who are eager indeed to study and expand their knowledge in the discovery level of understanding the nature of chemistry materials. Such guide will involve at least two to three parts of knowledge and skills consisted of the origin of life, electronics of molecular system (MES), and precise or accurate measurements. By implementing these advices, one believes the progress of applied physics frontier works in analytical chemistry will soon obtain a good harvest in the near future.